Macroeconomics determinants of Malaysia housing price / Nur Nabila Saparudin - Saparudin, Nur Nabila (Faculty of Business Management, 2014)
This paper aim at finding out determinants factors affecting housing price in Malaysia. The determinants are being measure in order to know whether it affect the price of housing in Malaysia. Interact software package E-view would be used for the testing and analysing the data collected. The determinants are flaws within gross domestic product (GDP, population, inflation rate and lending interest rate (IR). The study is an attempt to investigate and examine the housing price volatility in Malaysia over 1989-2012. Findings from previous research papers mostly on an in-depth understanding of house price volatility that is essential for housing investors and the policy makers (government). This study also has the implications for the investors and policy makers in which housing investors should estimate the conditional variance of a housing market in respect to the volatility of housing series is not always constant over time. Furthermore, policy makers should address the importance of considering the sub-national factors in formulating the national housing policy. The analysis and result of this research are limited by the quality of the data. The result of this paper would provide us with the indicate view and the factors that can affect the volatility of housing price in Malaysia.